Effects of glucose-fructose versus glucose ingestion on stride characteristics during prolonged treadmill running - Wilson, P. B.; Ingraham, S. J. (Sports Biomechanics, 2016)
Scarce research has examined the effects of carbohydrate composition on running stride characteristics. On two occasions, 14 males and 6 females completed a 120-min sub-maximal run followed by a 4-mile time trial. Participants consumed glucose (GLU) or glucose-fructose (GLU-FRU) beverages supplying 1.3g/min carbohydrate. Substrate use, psychological affect [Feeling Scale (FS)], and stride characteristics (stride frequency, stride length, and contact time) were assessed. Effects were expressed as Cohens d (90% confidence limits [90% CL]). CLs for stride frequency differences at 53min (90% CL=0.04-0.21) and 113min (90% CL=0.02-0.24) did not cover 0, indicating a positive effect of GLU-FRU. However, effect sizes were small (d=0.13) and likely-to-very-likely trivial. Energy expenditure differences at sub-maximal end were very likely trivial (d=0.08; 90% CL=0.00-0.17), while FS ratings were possibly higher for GLU-FRU at 50 (d=0.19; 90% CL=-0.10-0.48) and 110min (d=0.16; 90% CL=-0.13-0.45). During the time trial, stride length was possibly higher with GLU-FRU (d=0.13; 90% CL=-0.08-0.33). Glucose-fructose co-ingestion has no significant effect on stride characteristics during constant-velocity running but may result in slightly higher stride length during self-paced running.